The association between medical spending and health status: A study of selected African countries - Bein, Murad (Malawi Med J, 2020)
BACKGROUND: The report from the World Health Organization (WHO) reveals that health spending worldwide remains highly unequal as more than 80% of the world's population live in low and middle-income countries but only account for about 20% of global health expenditure. Another report by the WHO on the state of health financing in Africa published in 2013 intimates that countries that are part of their member states are still on the average level in meeting set goals in financing key health projects. OBJECTIVE: The study set out to investigate the association between public and private spending and health status for eight selected African countries, namely Burundi, Eritrea, Ethiopia, Kenya, Rwanda, Sudan, Tanzania and Uganda. Health status indicators include the incidence of tuberculosis, mortality rates, maternal deaths and prevalence of HIV. METHODS: Descriptive statistics and pairwise correlation are used to assess the relationship between healthcare spending and health status. Random and fixed effect models are further employed to provide insights into the association between descriptive statistics and pairwise correlation. We used annual data from the year 2000 to 2014 obtained from world development indicators. RESULTS: The relationship between healthcare spending (public and private) and health status is statistically significant. Public healthcare expenditure has a higher association than private expenditure in reducing the mortality rate, tuberculosis and HIV for the average country in our sample. For example, an increase in public healthcare spending is negatively associated and statistically significant at 5% or better in reducing female mortality, male mortality, tuberculosis and HIV. Private healthcare spending is more impactful in the area of maternal deaths, where it is associated negatively and statistically significant at 1%. An increase in private healthcare spending is linked to a reduction in maternal deaths. We also compared the association between an increase in healthcare spending on males versus females and observed that public health expenditure impacts the health status of both sexes equally, however, private health expenditure provides a greater positive benefit to males. It is worth remembering that two goals of the United Nations agenda on sustainable development are gender equality and ensuring healthcare for all. CONCLUSION: The findings of this research call for the selected African countries to pay more attention to public healthcare expenditure in order to improve health status, especially since private healthcare which provides access to healthcare facilities for some poor people leads to costs that are a burden. So, future research should focus on analyzing components of private healthcare spending such as direct household out-of-pocket spending, private insurance and direct service payments by private corporations as dependent variables to understand what form of private investment should be encouraged.